Overlapping flowering periods among Shorea species and high growth performance of hybrid seedlings promote hybridization and introgression in a tropical rainforest of Singapore - Kenzo, Tanaka (2020)
A considerable extent of interspecific hybridization among dominant canopy dipterocarp species was recently found in a tropical rain forest fragment in Singapore. However, information about the fertility of the hybrids and the growth of their successive hybrids remains limited. We studied the flowering phenology of four dipterocarp species in the genus Shorea (S. curtisii, S. leprosula, S. parvifolia, and S. macroptera) and two hybrids (S. curtisii × S. leprosula and S. leprosula × S. parvifolia) and studied the performances of seedlings reproduced from them. We observed that S. macroptera bloomed first, without overlap with congeneric species, followed by the other Shorea species and the two first filial (F1) hybrids. S. curtisii and S. leprosula, the species forming hybrids are most likely to succeed in this forest, completely overlapped with their hybrids. Fruits collected from the hybrids were viable, and these hybrid seedlings showed greater survival and a higher growth rate than those from pure species under greenhouse conditions. They included various cross types such as a backcross with each parent species. These results may imply that successive hybrids and introgression spontaneously occur among Shorea species. It may be important to consider the risk of hybridization for the management of tropical forests, particularly in degraded tropical rainforests where mechanisms of ecological isolation between closely related species might be altered.